Teachers' Ability in Building Students' Learning Readiness in Madrasah - Hartati, Zainap; Hamdanah, Hamdanah; Wahdarohmah, Nabila Khairunnisa (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2025)
As a teacher today has various challenges that are not easy, in addition to facing various administrative demands, teachers also face challenges from students who have diverse characteristics, one of which is technological advances. For this reason, the aim of this research is how teachers can develop students' learning readiness at MAN Kotawaringin Timur. This research offers that religion teachers need to have various abilities in order to build student readiness, considering the condition of students when they tend to have low motivation and interest. The purpose of the study is how the teacher's ability to build student learning readiness at MAN Kotawaringin Timur. This research uses quantitative with a descriptive approach and data collection techniques using observation, interviews, documentation and surveys, then to validate the data researchers use source triangulation techniques and techniques while data analysis uses percentages, data reduction and conclusions. The results of this research show that the ability of Al-Qur'an Hadith teachers is considered very good (86.39). This is because in opening lessons the teacher is able to create the right conditions so that students can focus on learning, the teacher also actively provides responses or reinforcement to students, besides that the teacher also explains the material systematically so that it is easily understood by students and the teacher also uses various variations in explaining the subject matter as well as the ability to manage the class, the process of guiding students well. While the ability of Fiqh teachers in building students' learning readiness is considered very good (85.83), this is because teachers are able to apply good lesson opening skills, questioning skills and reinforcement skills so as to increase student participation and interest in learning, explaining skills and organizing skills and individual learning skills as a way of building student learning readiness. This is because teachers have applied basic teaching skills as an ability to build students' learning readiness. In addition, teachers are able to apply lesson opening skills, questioning skills, reinforcement skills, explaining skills, variety skills and individual learning skills as a way to build student learning readiness. The results of this study can provide implications for schools and teachers as a reference to improve optimal student learning outcomes.